The time-image - Deleuze, Gilles, 1925-1995; Tomlinson, Hugh; Galeta, Robert (London ; New York : Bloomsbury Academic, 2013)
"The second volume of Gilles Deleuze's landmark reassessment of the art of film, now available in the Bloomsbury Revelations series"--
-- Preface to the English Edition Translator's Introduction 1. Beyond the Movement-Image 2. Recapitulation of Images and Signs 3. From Recollections to Dreams: Third Commentary on Bergson 4. The Crystals of Time 5. Peaks of Present and Sheets of Past: Fourth Commentary on Bergson 6. The Powers of the False 7. Thought and Cinema 8. Cinema, Body and Brain,Thought 9. The Components of the Image 10. Conclusions Notes Glossary Index.
"English translation first published in 1989 by The Athlone Press"--T.p. verso.
Includes bibliographical references and index.
Keywords: Motion pictures -- Philosophy